The Challenge of Pancasila in the Development of the Millennial Generation - Masruri, Masruri (Jurnal Scientia Indonesia, 2017)
Pancasila has grown and developed as the nation's ideology since the beginning of independence. And become a noble value for Indonesia as well as a unifying basis for the nation. It contains divine, humanitarian, unifying and democratic values that build social welfare. These fundamentals have built Indonesia to its present day. The millennial generation as the nation's next generation must be able to preserve and maintain the integrity of the values contained in Pancasila, lest the values of Pancasila just disappear without a trace. Various challenges must be able to be resisted, must be able to be conquered. The millennial generation must be able to prove that they are a generation that can be proud and can be trusted to carry a heavy burden towards a better Indonesia. In the current era, the value of Pancasila has begun to be forgotten by the millennial generation, they are more influenced by foreign cultures because they think that foreign cultures are more relevant to today's life. In this era, the development of science and technology and foreign culture is very easy to spread through online media for the consumption of the millennial generation, including the influence of radicalism and intolerance. Thus it is easy and poisons the soul of Pancasila. This is where we are tested how to continue to uphold Pancasila as an up-to-date ideology of the times, how to practice Pancasila in the modern era. In order for the millennial generation to continue to have a Pancasila foundation, an understanding of Pancasila ideology is needed, this can be obtained through formal, informal education and in everyday life.